2020
DOI: 10.1007/s10877-020-00459-1
|View full text |Cite
|
Sign up to set email alerts
|

A brief airway occlusion is sufficient to measure the patient’s inspiratory effort/electrical activity of the diaphragm index (PEI)

Abstract: Pressure generated by patient's inspiratory muscles (Pmus) during assisted mechanical ventilation is of significant relevance. However, Pmus is not commonly measured since an esophageal balloon catheter is required. We have previously shown that Pmus can be estimated by measuring the electrical activity of the diaphragm (EAdi) through the Pmus/EAdi index (PEI). We investigated whether PEI could be reliably measured by a brief end-expiratory occlusion maneuver to propose an automated PEI measurement performed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Electrical activity of the diaphragm (EAdi) provides important information about the crural diaphragm. The P mus /EAdi (PEI) index characterizes the pressure generated by the respiratory muscles in relation to the electrical activity of the diaphragm, which facilitates the discrimination between the respiratory drive (electrical activity) and the respiratory effort (generated pressure) [50,51]. The limitation of EAdi measurement lies in its invasiveness, but small-sample clinical studies confirmed a significant correlation between EAdi and the diaphragmatic electrical activity measured by surface electromyography [52,53].…”
Section: Identification Of Risk Factors For the P-sili Developmentmentioning
confidence: 99%
“…Electrical activity of the diaphragm (EAdi) provides important information about the crural diaphragm. The P mus /EAdi (PEI) index characterizes the pressure generated by the respiratory muscles in relation to the electrical activity of the diaphragm, which facilitates the discrimination between the respiratory drive (electrical activity) and the respiratory effort (generated pressure) [50,51]. The limitation of EAdi measurement lies in its invasiveness, but small-sample clinical studies confirmed a significant correlation between EAdi and the diaphragmatic electrical activity measured by surface electromyography [52,53].…”
Section: Identification Of Risk Factors For the P-sili Developmentmentioning
confidence: 99%
“…Thus, there is a paucity of evidence to define reference values for weakness or for optimal diaphragm activity during mechanical ventilation using EA di . Normalizing EAdi based on airway occlusion pressure offers a promising approach [35].…”
Section: Diaphragm Electromyographymentioning
confidence: 99%
“…The correction factor (/1.5) is required, because in the presence of an occlusion, the diaphragm generates more pressure for the same EAdi than with an open airway [26]. NME calculations over a brief airway occlusion of 200 ms at inspiratory onset tightly reflect NME occl [78], and estimate inspiratory effort. A change in NME could also indicate recruitment of accessory respiratory muscles, since EAdi is insensitive to recruitment of accessory muscles.…”
Section: Estimates Of Breathing Effortmentioning
confidence: 99%